2008 the Eighth IAPR International Workshop on Document Analysis Systems 2008
DOI: 10.1109/das.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

An End-to-End Administrative Document Analysis System

Abstract: This paper presents an end-to-end administrative document analysis system. This system uses case-based reasoning in order to process documents from known and unknown classes. For each document, the system retrieves the nearest processing experience in order to analyze and interpret the current document. When a complete analysis is done, this document needs to be added to the document database. This requires an incremental learning process in order to take into account every new information, without losing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Nowadays, this task is especially important because huge volumes of documents are scanned to be processed in an automatic way. Some automatic solutions based on optical character recognition (OCR), bank check reader, postal address reader and signature verifier, have already been proposed but a lot of work has still to be done to classify other types of documents such as tabular forms, invoices, bills, and receipts [20]. Chen and Blostein [21] presented an excellent survey on document image classification.…”
Section: Document Image Similaritymentioning
confidence: 99%
“…Nowadays, this task is especially important because huge volumes of documents are scanned to be processed in an automatic way. Some automatic solutions based on optical character recognition (OCR), bank check reader, postal address reader and signature verifier, have already been proposed but a lot of work has still to be done to classify other types of documents such as tabular forms, invoices, bills, and receipts [20]. Chen and Blostein [21] presented an excellent survey on document image classification.…”
Section: Document Image Similaritymentioning
confidence: 99%
“…Alternatively, we have considered lines and logos as noise to be removed, and focused our document image analysis on text elements, which has proven to be more robust and computationally efficient. -In other works [1,11,12,16] we find the utilization of Attributed Relational Graphs to represent document models, assuming that connecting nodes exactly above, below, left or right of each other can be detected. We have observed that such regularity is not observed in practice in many situations.…”
Section: Related Workmentioning
confidence: 99%
“…Hamza et al [11,12] have built a system, further developed by Belaïd et al [1], in which features are extracted and grouped together using a bottom-up approach. Keywords are segmented and grouped together with neighbouring keywords generating a high level structure.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We are thus faced with a 'plasticity/stability' dilemma -can a GNG network learn new data without using the data it learnt before and without deterioration of the network that has already been generated? An incremental GNG was developed (Prudent and Ennaji, 2004) and improved by Hamza et al (2008). It allows data to be learnt in parts if the database is too large to be learnt in one go and thus allows the learning process to be restarted even if the data learnt previously is no longer accessible.…”
Section: Neural Modelsmentioning
confidence: 99%